India and Germany: Global Partnership in 21st century (International Journal of Scientific Research and Management (IJSRM), 2015)
Nehru and Adenauer established diplomatic relations in 1951. After an auspicious beginning in the earlyperiod, relationship between India and Germany were caught in the stagnations of benign neglect from 1960s to1980s. Following the India’s economic reforms and subsequent economic growth attracted the interest of Germany.India is Germany’s most important scientific and technological cooperation partner in South Asia and both countrieshave entered a strategic partnership in education, science and research which offers the basis for diverse forms ofcooperation. How will these two central powers in the world interact with each other in 21st century? The paperfocuses on to promote an extensive understanding of the Indo-German perspectives for mutual relations as well as theforeign policy outlooks in a changing international milieu. The main issues will be to widen the existing edifice tocover traditional and non-traditional security issues. Also, it is essential and time for both India and Germany to movethe relations beyond the purchase of BMW and Mercedes car.